Evaluating microbial safety, postharvest quality, and consumer acceptability of fresh produce engraved with QR codes using a CO₂ laser labeling technology - Khadka, Durga (Kansas State University, 2023)
Fresh produce is traditionally labeled with plastic price lookup (PLU) stickers that are attached to the produce surface using edible glue. However, both the stickers and glue are environmental contaminants, and the stickers can detach from the produce surface during handling and disrupt the food traceability system. An alternative method of labeling, the CO₂ laser labeling technology (LLT), widely used in other industries (e.g., automotive, healthcare, etc.) for engraving information on various surfaces, has been gaining attention in the horticultural industry lately. However, due to large variations among produce types (size, shape, color), the performance of this technology varies, and little information is known about its effects on postharvest quality, microbial safety, and consumer acceptability. The first chapter of the thesis provides background information on the importance of food traceability, methods of produce labeling, and the potential of new alternative CO₂ LLT. The second research chapter focused on investigating the effect of CO₂ LLT on i) postharvest quality, ii) microbial safety of fresh produce, and iii) economic analysis of this technology. Three horticultural crops, ‘Red Delicious’ apples, green bell peppers (Capsicum annuum), and cucumbers (Cucumis sativus) were procured from a local grocery store. Each produce item was engraved with a Quick Response (QR) code or 6-digit alphanumerical (text) code using the commercially available Trotec Speedy 300 CO₂ laser engraver, followed by the application of edible wax. Fresh weight loss for laser-labeled produce was higher than the nontreated control, but no difference in visual quality ratings was observed compared to the control. The laser-labeled produce was assessed for microbial contamination by artificially inoculating rifampicin-resistant Escherichia coli (E. coli) at the initial concentration of log 6 colony forming unit (CFU)/mL to the labeled fruit. The results showed that the population of rifampicin-resistant E. coli in QR-code labeled apples was statistically similar to the control. The third research chapter assessed consumers' perception and acceptability of the laser-labeled ‘Red Delicious’ apple (Malus domestica) fruit. A consumer study (N=75) was conducted to assess consumers' perception and acceptability of laser-labeled apples with three treatments: 1) apple with QR-code printing, 2) apple with PLU plastic sticker, and 3) non-labeled control. A randomized set of the three treatment samples was given to respondents at the Sensory and Consumer Research Center facility at Kansas State University, Olathe. The ranking of three treatments based on overall physical quality revealed that before providing educational information on product labeling, consumers ranked QR-code labeled apples as the lowest group, followed by sticker-labeled and unlabeled apples. In contrast, after sharing information on the CO₂ LLT, the ranking scores from the same consumers were statistically similar. Results indicate that CO₂ LLT has the potential for industrial application from the consumers' perspective, and providing consumer education seems essential to make this technology more accepted by consumers.
Keywords: Price Look Up; Produce labeling; Food traceability; Apple; Cucumber; Green bell pepper